Relative Contributions of Myostatin and the GH/IGF-1 Axis in Body Composition and Muscle Strength - Lozier, Nicholas R.; Kopchick, John J.; de Lacalle, Sonsoles (Frontiers in Physiology, 2018)
Myostatin, a negative regulator of muscle growth, is considered a potential therapeutic agent for individuals suffering from various muscle wasting and strength declining diseases because inhibiting Mstn signaling leads to muscular hypertrophy. In this study we investigate the interaction between myostatin and the growth hormone/insulin-like growth factor-1 (GH/IGF-1) axis in muscle function and strength. To this end, we measured hind limb grip strength and myostatin levels in two mouse models of GH gene manipulation; GH receptor knockout (GHR-/-) mice which have reduced GH/IGF-1 action, and bovine GH transgenic (bGH) mice which have excess GH/IGF-1 action. We found that specific muscle force was significantly reduced in bGH mice, and significantly increased in GHR-/- mice, compared to their respective littermate wild type controls. The expression of the mature form of myostatin was significantly increased in bGH mice, and unchanged in GHR-/- mice. In the bGH mice, the high levels of mature myostatin were accompanied by increase body weight and lean mas, consistent with other published results indicating that the IGF-1 signaling pathway is dominant over that of Mstn. Our results also suggest that in these mouse models there is an inverse relationship between muscle strength and levels of myostatin and GH, since constitutive overexpression of GH resulted in elevated levels of mature myostatin in muscle, accompanied by a reduction in strength. By contrast, in the GHR-/- mice with reduced levels of IGF-1, mature myostatin levels were unchanged and muscle strength was increased.